In-Process Surface Roughness Recognition (IPSRR) system using Acoustic Emission (AE), Part III - Samuel, Edward Atit (Universiti Malaysia Sarawak (UNIMAS), 2005)
Monitoring surface roughness using acoustic emission is to enable faulty conditions related with surface roughness to be recognized during the process before the quality of end product is out of specification. This report contain the study effect of different cutting parameters such as spindle rotation speeds. cutting feed rates and depth of cut in turning process to the surface finish of the specimen. mild steel. Comparison in many different cutting conditions is also done to study the effects such as cutting with sharp and wear tool, and cutting with and without coolant. The acoustic emission generated from the cutting process is recorded and the average, peak to peak and standard deviation value is calculated. These values is then analyze as a source for monitoring the surface roughness by comparing it with the surface roughness measurement in arithmetic mean value, Ra.